CLASSIFYING THE READABILITY LEVEL OF READING TEXT ON ENGLISH TEXTBOOK ENTITLED “PATHWAY TO ENGLISH” - Rahmi, Ulfa; Riza, Armilia; Yelliza, Yelliza (TELL - US JOURNAL, 2022)
Reading was an activitythat could not be separated  from teaching andlearning activities. It cause the textbook was one of source in learning. In this case, each reading texts had different difficulties, so it was important for teacehrs to chose appropriate text for students so they would comprehended the text. Based on the phenomenon, the researchers interested to conduct a study that aimed to classified the readability of reading text on English textbook entitled "Pathway to English" for class XI for interest group. The researchers found 22 reading text. This study used a descriptive research method with a quantitative approach. In calculating the readability level, the researchers used the Flesch Reading Ease formula (6 levels). The result of readability level analysis on reading texts showed there were 6 categorizes of readability levels, namely easy, fairly easy, standard, fairly difficult, difficult and very difficult. The classification of reading texts were easy 2 texts, fairly easy 2 texts, standard 7 texts, fairly difficult 6 texts, difficult 4 texts and very difficult 1 text.